THE UNITY OF QUR’ANIC THEMES: Historical Discourse and Contemporary Implications for Tafsīr Al-Mawḍū'ī Methodology (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
The discourse concerning whether the Qur'an possesses thematic unity has persisted as a subject of prolonged debate throughout history up to the present day. While the majority acknowledges this unity, a minority rejects it. These contrasting perspectives bear significant implications for the methodology of tafsīr al-mawḍū'ī (thematic exegesis): namely, the robustness or fragility of this method. Consequently, this paper examines the historical discourse on Qur'anic thematic unity, contextualizing it with the methodology and urgency of tafsīr al-mawḍū'ī in the modern context to strengthen the foundations of this method. After applying the principles of literature review utilizing historical analysis, this study demonstrates that the discourse on Qur'anic thematic unity falls under the terms naẓm (coherence), siyāq (context), and munāsabah (correlation) in 'ulūm al-qur'ān (Qur'anic sciences), as well as the theory of istiqrā' (induction) in uṣūl al-fiqh (principles of Islamic jurisprudence), all of which are relevant as analytical tools for tafsīr al-mawḍū'ī. Thus, this paper has implications for strengthening the arguments of the group that accepts the unity of meaning in the Qur'an while simultaneously reinforcing the methodological foundations of tafsīr al-mawḍū'ī.